HUBUNGAN PENGETAHUAN MENJAHIT DENGAN KEMAMPUAN MENJAHIT ROK PADA REMAJA BINAAN DI UPT PS ANAK REMAJA TANJUNG MORAWA - Farihah, Farihah; Andriaani, Siska (Universitas Negeri Medan, 2014)
ABSTRACTThis research aimed to find out (1) sewing knowledge; (2) sewing skirt skill; (3) the relationship of sewing knowledge to thesewing skirt skill. This research was conducted in March 2014. Research Locations was at Tanjung Morawa . Sampling total is 41 teenagers, with the method of data collection using sewing knowledge test and observation to sewing skirt skill. Data analysis using descriptive techniques, requirements analysis using normality, linearity and hypotheses tests to product moment correlation. The result is shown the knowledge of sewing is 51.22 % and skill to sew skirt is 100% belong to category tend to be high. To test the data normality using the chi-square formula in the level of 5% with df = 6, is obtained sewing knowledge variables were normally distributed 11,070 â‰¤ 2.31) and sewing skirt ability variables were normally distributed (3.31 â‰¤ 11,070). While the linearity and the significance tests of the regression equation, for regression equation y and x is obtained y: 83.86799 + 0.101X have a significant relation5% is Fcalculate< Ftable(4.834 > 4.09) and linearity test Fcalculate< Ftable(2.10 < 2.13). From the result of correlation analysis is conducted rwy 0.332 > 0.308. Thus rxy>rtable or 0.332> 0.308. It is concluded that there is a significant relationship of sewing knowledge with sewing skirt skill. Kata Kunci : Pengetahuan menjahit, kemampuan menjahit rok.